A nevrose do poeta: da poesia como hýbris na literatura de Cruz e Sousa - Alice Vieira Barros (2018)
This masters thesis aims at discussing the image of the poet as it appears in João da Cruz e Sousas works and at analyzing the authors reflexions about the act of creation in poetry. Starting from the analogy between the life of the poet and the mystical life, which is present throughout these poetical work, it tries to understand the representation of the artists trajectory in Cruz e Sousas poems as a kind of sacerdotal office. The central hypothesis advances the possibility of intersections between the mystic and the poet. One of the most important intersections is related to the connection between the image of the poet and that of Santa Teresa dÁvila a mystic often evoked by the author. We try to verify if Cruz e Sousas ideas about the act of creation in poetry may be associated with the way Santa Teresa regarded her mystical experience of extasis, starting from the premise that both the poet and the saint are taken by a sort of hýbris for the poet, in language; for the saint, in the Spirit.